Gabe Jones: Marvel Comics’ greatest jazz musician - Jiménez-Varea, Jesús (Jazz Research Journal, 2022)
Introduced in the 1963 Marvel comic Sgt. Fury and His Howling Commandos, Gabe Jones is ‘one of the first “normal” black people in comics. […] I mean not a racist caricature’, in the words of African-American writer Reginald Hudlin. The Harlem-born Jones was written as a professional jazz trumpeter who had learned to play from none other than Louis Armstrong. At some point during the Second World War, the Howling Commandos help repel a Nazi invasion of Wakanda, the African nation ruled by Marvel superhero Black Panther, with whom Jones strikes up a personal friendship. This piece takes the form of a 1000-word entry on Jones for a fictional Encyclopedia of Jazz Marvels. It speculates the effect that contact with an Afrofuturist utopia like Wakanda might have had on the subsequent evolution of an African-American jazz musician, leading to the birth of an imagined genre—Vibop—in the early 1950s. By parodying the formal qualities of journalistic writing on music and comics, the piece speculates on the boundaries of fiction in jazz life-writing.